Does fibrin(ogen) bind to monomeric or dimeric GPVI, or not at all?. (3rd April 2019) - Slater, Alexandre; Perrella, Gina; Onselaer, Marie-Blanche; Martin, Eleyna M; Gauer, Julia S; Xu, Rui-Gang; Heemskerk, Johan WM; Ariëns, Robert A S; Watson, Steve P
Abstract: GPVI is the major signalling receptor for collagen on platelets. Dimerization of GPVI is required for collagen binding and initiation of signalling through the associated FcR-γ chain. Recently, fibrin and fibrinogen have been identified as ligands for GPVI and shown to induce signalling in support of thrombus formation and stabilization. Contrasting observations have been reported on whether fibrin binds to monomeric or dimeric GPVI, or to neither form. In this article, we discuss reasons for the contradictory results and how to reconcile these. We conclude that a lack of structural knowledge regarding the GPVI constructs that are being used, along with the use of non-standardized reagents, might be the main cause of the discrepant results. This article aims to highlight some of the key areas that need to be addressed.